2010
DOI: 10.1089/jmf.2009.0247
|View full text |Cite
|
Sign up to set email alerts
|

Topical and Systemic Anti-Inflammatory Effects of Echinodorus macrophyllus (Kunth) Micheli (Alismataceae)

Abstract: Echinodorus macrophyllus leaf has been used in Brazilian folk medicine to treat inflammatory conditions and kidney dysfunctions. The present study evaluated the effects of leaf ethanolic extract from E. macrophyllus (EEEm) in acute and subchronic models of inflammation. The EEEm was found to cause significant and potent inhibition of carrageenan- and dextran-induced paw edema in rats and marked decreases in the exudate volume and leukocyte migration in rats with carrageenan-induced pleurisy, the vascular perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
5
11
0
4
Order By: Relevance
“…Flavones, flavonoids, xanthones, diterpenes, triterpenes and steroids have been described in E . macrophyllus extracts . In previous studies, we confirmed the presence of polyphenols on E. macrophyllus leaves using techniques described by Marini‐Bettòlo et al .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Flavones, flavonoids, xanthones, diterpenes, triterpenes and steroids have been described in E . macrophyllus extracts . In previous studies, we confirmed the presence of polyphenols on E. macrophyllus leaves using techniques described by Marini‐Bettòlo et al .…”
Section: Discussionsupporting
confidence: 83%
“…[15] Later, several pharmacological effects of the ethanolic extract of E. macrophyllus (EEEm) were also demonstrated, including potent inhibition of carrageenan-and dextran-induced rat paw oedema; decrease of exudate volume and leucocyte migration in rats with carrageenan-induced pleurisy; inhibition of mouse ear oedema induced by topical use of croton oil; and reduction of high vascular permeability induced by intraperitoneal injection of acetic acid. [16] In this work, using the air pouch model of inflammation, it was showed that the fractionation of AEEm provided a more potent anti-inflammatory fraction (Fr20) capable of reducing LTB4 release, protein level and leucocyte migration in exudate, as well as in-vitro NO production and neutrophil migration.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Containing flavonoids, they have been used for thousands of years in Eastern medicine, have antioxidant activity and protective function in the treatment of diseases mediated by reactive oxygen species. (19,20) The Echinodorus macrophyllus, described by its antioxidant and anti-inflammatory action, stands out. It is rich in flavonoids, confirmed by the phytochemical analysis of the leaves.…”
Section: Discussionmentioning
confidence: 99%
“…It is rich in flavonoids, confirmed by the phytochemical analysis of the leaves. (19) In this context, it was observed that the antioxidant action of the Echinodorus macrophyllus phytomedicine attenuated the decrease in renal function and the reduction of levels of peroxides and aldehydes from the lipid peroxidation. Similar results of antioxidant protection of the Echinodorus macrophyllus were found in studies carried out with the model of acute kidney injury induced by gentamicin.…”
Section: Discussionmentioning
confidence: 99%